2017
DOI: 10.1021/acs.est.7b03367
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardants and Plasticizers in Building and Decoration Materials and Their Potential Burdens in Newly Decorated Houses in China

Abstract: Organophosphorus flame retardants (OPFRs) have been increasingly used in various building and decoration materials to fulfill fire safety standards since the phasing out of polybrominated diphenyl ethers. We determined OPFR concentrations in the most commonly used building and decoration materials available in local markets and online in China. The OPFR concentrations varied significantly, from 14.78 ng/g (putty powder) to 9649000 ng/g (expanded polystyrene panel (EPS)). Relatively high concentrations of OPFRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The use of TCEP, TCIPP and TDCIPP in a range of 18 building and decoration materials (n=56) was evidenced by the presence of Cl-PFRs in all samples which included wallpaper, powders, paints, boards, sealing materials PVC line and foams [90]. Concentrations of Cl-PFRs were significantly higher in foams than other materials, with levels ranging from 2-121 µg/g TCEP, 170-9510 µg/g TCIPP and 7-65 µg/g TDCIPP.…”
Section: Chlorinated Pfrsmentioning
confidence: 99%
“…The use of TCEP, TCIPP and TDCIPP in a range of 18 building and decoration materials (n=56) was evidenced by the presence of Cl-PFRs in all samples which included wallpaper, powders, paints, boards, sealing materials PVC line and foams [90]. Concentrations of Cl-PFRs were significantly higher in foams than other materials, with levels ranging from 2-121 µg/g TCEP, 170-9510 µg/g TCIPP and 7-65 µg/g TDCIPP.…”
Section: Chlorinated Pfrsmentioning
confidence: 99%
“…Organophosphate esters (OPEs) are synthetic chemicals found in consumer products, including furniture, electronics, plastics, building materials, and processed foods ( Ballesteros-Gómez et al, 2014 ; Bello et al 2018 , 2010 ; Kajiwara et al 2011 ; Poma et al 2017 ; Stapleton et al 2009 ; Wang et al 2017 ; Yang et al 2019 ). National biomonitoring data indicate that exposure to OPEs is widespread in the U.S. general population ( Ospina et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average concentrations of PBDEs, NBFRs, OPEs, SCCPs, MCCPs, and HMs in all PCMP samples were 6.40 ng/g, 144 ng/g, 10.1 μg/g, 3.58 μg/g, 3.17 μg/g, and 72.3 μg/g, respectively. On comparing the concentration of PTSs in other studies, it is found that the concentration of PBDEs was much lower than the plastics retained on the South China Sea island (22 μg/g); the concentration of OPEs was similar to the plastic decoration materials (44.5 μg/g) . The concentrations of SCCPs and MCCPs were lower than those in rubber track products (3.64 and 41.4 mg/g) but higher than those in Chinese plastic food packaging (188 and 644 ng/g) …”
Section: Resultsmentioning
confidence: 87%